Role of educational multimedia content in the formation of student khowledge - Mukhsinov, Shamil; Khairullaev, Zafar (MMIT Proceedings, 2024)
This article examines educational multimedia content, their peculiarities and points of view for involvement in education in the process of forming student knowledge.